Dynamics of blood neutrophil‐related indices during nivolumab treatment may be associated with response to salvage chemotherapy for non‐small cell lung cancer: A hypothesis‐generating study. Issue 2 (23rd December 2018) - Soda, Hiroshi; Ogawara, Daiki; Fukuda, Yuichi; Tomono, Hiromi; Okuno, Daisuke; Koga, Seiko; Taniguchi, Hirokazu; Yoshida, Masataka; Harada, Tatsuhiko; Umemura, Asuka; Yamaguchi, Hiroyuki; Mukae, Hiroshi
Abstract : Several recent studies have shown that salvage chemotherapy following PD‐1 blockade produces high antitumor activity in some patients with non‐small lung cancer (NSCLC). However, the underlying synergistic mechanisms remain uncertain. The blood neutrophil‐to‐lymphocyte ratio (NLR) and absolute neutrophil count (ANC) can reflect the number of circulating myeloid‐derived suppressor cells and tumor‐associated neutrophils. The immunosuppressive status of the tumor microenvironment could be monitored by the time‐series patterns of NLR and ANC. The dynamics of NLR and ANC during nivolumab treatment were retrospectively explored in 15 patients: 8 patients receiving subsequent salvage chemotherapy (2 groups: 3 non‐responders and 5 responders), and 7 responders to nivolumab alone (2 groups: 4 partial response and 3 complete response). The dynamics of NLR and ANC during nivolumab differed among these four groups (NLR P = 0.045, ANC P = 0.067). NLR and ANC during nivolumab treatment increased over time in non‐responders to salvage chemotherapy, with an inverse relationship between drug response and NLR or ANC at four to six weeks among the four groups. We hypothesize that the early dynamics of NLR and ANC during nivolumab may be associated with the late efficacy of subsequent salvage chemotherapy. Further studies involving a large cohort are needed to confirm these findings, which could provide insight into the role of myeloid immunosuppressor cells in combination PD‐1 blockade and chemotherapy.